2 - Informing Approaches in Establishing Stand Alone Community Literacy Programmes in South Africa: DOI: 10.4314/ad.v29i3.22198 - Kanyane , Chris (Africa Development, 2004)
Literacy is usually considered the ability to read at a basic level. Now it is beginning to be defined more broadly to include applying reading, writing, and mathematical skills to obtain and use information and solve problems at levels of proficiency necessary to function in society, to achieve one's goals and develop one's knowledge and potential. 'Family Literacy' is an intergeneration approach to literacy activities. Comprehensive family literacy services provide a holistic, fully integrated, family-focused approach, providing parents and children most in need of improving their literacy skills with intensive, frequent and long-term educational and non-educational services. Through the Technikon Northern Gauteng Research Capacity Building project, I initiated the Soshanguve Family Literacy programme in the surrounding community of Soshanguve. The Soshanguve Family Literacy Programme provides the following activities: Adult Education, Childhood Education or Program Your Child for Success, Parent Education, Interactive Parent/Child Activities (PACT TIME).